Chemistry - Martin S. Silberberg (McGraw-Hill, 2009)
With each edition, Chemistry: The Molecular Nature of Matter and Change by Martin Silberberg is becoming a favorite among faculty and students. Silberberg's 5th edition contains features that make it the most comprehensive and relevant text for any student enrolled in a general chemistry course. The text contains unprecedented macroscopic to microscopic molecular illustrations, consistent step-by-step worked exercises in every chapter, and an extensive range of end-of-chapter problems which provide engaging applications covering a wide variety of freshman interests, including engineering, medicine, materials, and environmental studies. All of these qualities make Chemistry: The Molecular Nature of Matter and Change the centerpiece for any General Chemistry course